Social Interaction Among Employees at the Youth and Sports Office of Maluku Province - Muhammad Pascal Hanggoro; Elsina Titaley; Dominggus E. B. Saija (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This qualitative descriptive research aims to determine and analyze patterns of social interaction among employees at the Maluku Province DISPORA Office. The research was conducted at the Office of the Department of Youth and Sports (DISPORA) of Maluku Province, Ambon City, Maluku. Using primary and secondary data sources, data collection techniques were carried out through observation, in-depth interviews, and documentation. The data obtained were then analyzed using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion. The results showed that social interaction among employees of the Maluku Provincial Youth and Sports Office occurs in two patterns. Firstly, the pattern of associative social interaction manifests as cooperation, solidarity, sectional coordination, and intimate informal relationships. Second, dissociative interaction patterns manifest as conflicts arising from workload inequality, dissent, and competition.